2015
DOI: 10.1021/acs.jafc.5b03730
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus licheniformis Isolated from Traditional Korean Food Resources Enhances the Longevity of Caenorhabditis elegans through Serotonin Signaling

Abstract: In this study, we investigated potentially probiotic Bacillus licheniformis strains isolated from traditional Korean food sources for ability to enhance longevity using the nematode Caenorhabditis elegans as a simple in vivo animal model. We first investigated whether B. licheniformis strains were capable of modulating the lifespan of C. elegans. Among the tested strains, preconditioning with four B. licheniformis strains significantly enhanced the longevity of C. elegans. Unexpectedly, plate counting and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Certain probiotic bacteria have been shown to increase the lifespan of C. elegans (Grompone et al, 2012; Park et al, 2015) but our isolate had the opposite effect on T. castaneum . Furthermore the fertility of the beetle was also reduced following treatment with the E. mundtii isolate.…”
Section: Discussionmentioning
confidence: 59%
“…Certain probiotic bacteria have been shown to increase the lifespan of C. elegans (Grompone et al, 2012; Park et al, 2015) but our isolate had the opposite effect on T. castaneum . Furthermore the fertility of the beetle was also reduced following treatment with the E. mundtii isolate.…”
Section: Discussionmentioning
confidence: 59%
“…According to our hypothesis, Park et al (2014) observed that newly isolated strains of L. plantarum , which were more efficient in colonizing the nematode gut with respect to LGG, were able to extend the worm’s lifespan. However, this aspect is still controversial, since other authors reported a negative correlation between colonization capacity and lifespan extension (Brokate-Llanos et al, 2014; Park et al, 2015), or suggested that gut colonization does not directly influence the host defense response (Yun et al, 2014). It must be pointed out that in the case of E. coli as food source, the reduction of colonization capacity could lower bacterial pathogenicity resulting in an increased worm’s longevity (Brokate-Llanos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It must be pointed out that in the case of E. coli as food source, the reduction of colonization capacity could lower bacterial pathogenicity resulting in an increased worm’s longevity (Brokate-Llanos et al, 2014). Moreover, it has been observed that the effects of bacterial feeding on worm longevity are often strain-specific (Park et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments with mutant strains, ser-1, and ser-7 (serotonin receptor gene), tph-1 (tryptophan hydroxylase), mod-1 (serotoningated chloride channel), bas-1 (serotonin-and dopamine-synthetic aromatic amino acid decarboxylase), revealed that B. licheniformis has an impact on serotonin signaling system. The lifespan extension was mediated by the serotonin signaling [58].…”
Section: Anti-aging Property Of Probioticsmentioning
confidence: 99%